User identification: a key factor for elderly viewers to benefit from interactive television services - Silva, Telmo Eduardo Miranda Castelão da
The offer of interactive television services is becoming more and more frequent in regular households allowing a more customizable way of watching TV. However, in a multi-viewer environment a truly personalized TV experience could not merely rely on the identification of the STB that users have at their homes. For this purpose, a non-intrusive user identification technique is especially relevant, namely when senior viewers are at stake. In this work we are studying different approaches to perform an adequate identification of senior viewers so they can benefit from a series of interactive services targeted to their needs. To achieve this aim, a set of exploratory interviews have been carried out, and based on its results, a prototype with several identification technologies has been developed. With this prototype and through a set of usability tests we were able to collect relevant opinions about the type of added value TV services that this target audience desires. In addition, it was also possible to understand points of view that lead us to conclude that the user context involves a complex trade-off that influences the choice of the most suitable identification system.